If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 = -6(v + -4) + 2 Reorder the terms: 14 = -6(-4 + v) + 2 14 = (-4 * -6 + v * -6) + 2 14 = (24 + -6v) + 2 Reorder the terms: 14 = 24 + 2 + -6v Combine like terms: 24 + 2 = 26 14 = 26 + -6v Solving 14 = 26 + -6v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '6v' to each side of the equation. 14 + 6v = 26 + -6v + 6v Combine like terms: -6v + 6v = 0 14 + 6v = 26 + 0 14 + 6v = 26 Add '-14' to each side of the equation. 14 + -14 + 6v = 26 + -14 Combine like terms: 14 + -14 = 0 0 + 6v = 26 + -14 6v = 26 + -14 Combine like terms: 26 + -14 = 12 6v = 12 Divide each side by '6'. v = 2 Simplifying v = 2
| -1(1+7x)-6-7-1x=36 | | 6x+3-9x=3x+7 | | 12=2x-13 | | 11+5v=-7+13v | | 3x+9+7x=39 | | 7x^2+6x-16=0 | | 4(2x+7)=44 | | 12x-7+3x+3=180 | | x+22=5x+38 | | 33+3k=0 | | 4x^2+2x+27=0 | | 3+3=6x | | 3x+2(x+5)=7x | | 6(2b+5)= | | X+y-2z=-12 | | 12x-4+6x+8=2x+10 | | (2x+8)(6x^2+2x+1)= | | (c+1)(c-1)=0 | | (h+4)(2h-5)=0 | | 9x-3(x-1)=6+x | | n^3-n-1=0 | | 189=7(-6h-9) | | (3x-4)+2x=1 | | (X+7)(8x+5)=0 | | 3x+5-5y-15=0 | | -2(z+3)+-z=-z+-4(z+2) | | 3(x-1)=6x-4+2x-4x | | 12x-7=3x+2 | | 4.8-3z-2.3-z=-3z-6.6 | | 2(z+3)-z=-z-4(z+2) | | 33w+28=203-2x | | -9=4x-5 |